2021
DOI: 10.1177/20458940211056527
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of contributors to pulmonary hypertensive disease: impacts of whole lung and focal disease distributions

Abstract: Pulmonary hypertension (PH) has multiple etiologies, and so can be difficult to diagnose, prognose, and treat. Diagnosis is typically made via invasive hemodynamic measurements in the main pulmonary artery, and is based on observed elevation of mean pulmonary artery pressure. This static mean pressure enables diagnosis, but does not easily allow assessment of the severity of PH, nor the etiology of the disease, which may impact treatment. Assessment of the dynamic properties of pressure and flow data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
(368 reference statements)
0
4
0
Order By: Relevance
“…Colebank et al employed an exponential stiffness model, with values similar to those reported in Fig. 5 a. Ebrahimi et al ( 2021 ) simulated PAH and CTEPH conditions using a transmission-line model of the whole pulmonary circulation. These authors showed that a combination of vascular narrowing and changes in stiffness could replicate flow heterogeneity seen in clinical CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…Colebank et al employed an exponential stiffness model, with values similar to those reported in Fig. 5 a. Ebrahimi et al ( 2021 ) simulated PAH and CTEPH conditions using a transmission-line model of the whole pulmonary circulation. These authors showed that a combination of vascular narrowing and changes in stiffness could replicate flow heterogeneity seen in clinical CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…Network models can simulate remodeling in CTEPH Colebank et al (2021); Ebrahimi et al (2019Ebrahimi et al ( , 2021; Qureshi et al (2014). However, without accurate coupling to macro-vascular models, measurable changes in flow dynamics and shear stress in the largest pulmonary arteries cannot be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous CFD studies have suggested that the error in predicted spatially averaged WSS from static versus pulsatile simulations is small Kheyfets et al (2015). However, pulsatile simulations in the future would provide important insights into dynamic changes in the circulation, which may play a role in response to disease Ebrahimi et al (2021).…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation